2020
DOI: 10.1111/pai.13236
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, immunological features and follow up of 20 patients with dedicator of cytokinesis 8 (DOCK8) deficiency

Abstract: Biallelic mutations in the dedicator of cytokinesis 8 gene (DOCK8) cause a progressive combined immunodeficiency (CID) characterized by susceptibility to severe viral skin infections, atopic diseases, recurrent respiratory infections, and malignancy.Hematopoietic stem cell transplantation (HSCT) is only curative treatment for the disease. However, there is limited information about long-term outcome of HSCT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…Happel et al report similar results for 12 patients and detected allergen-specific mast cells through skin prick tests after HSCT [36]. Only few of our patients reported challenging prior food allergies post-HSCT; however, reintroduction of a diversified diet post-HSCT has been successfully reported for numerous other patients [28,[36][37][38]. The low incidence of allergic events post-HSCT, despite overall stable allergen reactivity on immunoblot, may be attributed to higher T-cell chimerism and a speculative role of regulatory T-cell (T reg ) functions.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Happel et al report similar results for 12 patients and detected allergen-specific mast cells through skin prick tests after HSCT [36]. Only few of our patients reported challenging prior food allergies post-HSCT; however, reintroduction of a diversified diet post-HSCT has been successfully reported for numerous other patients [28,[36][37][38]. The low incidence of allergic events post-HSCT, despite overall stable allergen reactivity on immunoblot, may be attributed to higher T-cell chimerism and a speculative role of regulatory T-cell (T reg ) functions.…”
Section: Discussionsupporting
confidence: 78%
“…Aydin et al reported on a large cohort of 81 patients with DOCK8 deficiency and HSCT on behalf of the inborn errors working party of EBMT and ESID with promising overall outcomes of HSCT [23]. More recently, Haskologlu et al reported on a Turkish cohort of 20 patients with DOCK8 deficiency of whom 11 patients underwent HSCT [28]. However, these and other reports have focused on survival, conditioning regimens, and transplant-related outcomes, rather than improvement of clinical aspects and immunologic reconstitution, particularly in patients with mixed chimerism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohort studies have reported around 50% probability to survive beyond 20 years of age with a mean age at death of 9–12 years ( Aydin et al, 2015 ; Zhang et al, 2014 ). The disease primarily presents with atopic disease, upper and/or lower respiratory infection, frequent viral cutaneous infections, and malignancy ( Figure 3 ) ( Zhang et al, 2009 ; Zhang et al, 2014 ; Aydin et al, 2015 ; Haskologlu et al, 2020 ). Mortality occurs primarily due to infectious agents particularly affecting the skin and respiratory tracts, followed by malignancy, and less commonly CNS vasculitis ( Aydin et al, 2015 ).…”
Section: Clinical Manifestations Of Dock8 Deficiencymentioning
confidence: 99%
“…DOCK8-deficiency leads to a predisposition of cancer, particularly subtypes of haematological or epithelial origin which are often virally-induced either by Epstein Barr Virus (EBV)-driven leiomyosarcomas and lymphomas, and/or Human Papilloma Virus (HPV)-associated squamous cell carcinomas ( Papan et al, 2014 ; Zhang et al, 2014 ; Aydin et al, 2015 ; Haskologlu et al, 2020 ) In the aforementioned cohort studies, 8–17% of patients had developed malignancies during the follow-up period, which included cases of lymphoma (Burkitt and non-Hodgkin lymphoma), squamous cell carcinoma, and sarcoma ( Zhang et al, 2014 ; Aydin et al, 2015 ).…”
Section: Clinical Manifestations Of Dock8 Deficiencymentioning
confidence: 99%